A utilização da metodologia ativa: aprendizagem baseada em projetos para a alfabetização ecológica nos anos iniciais - Backes, Marciani Teresinha Petry (2023)
Instituted by Law No. 9,795/1999 and established in school curricula in Paraná by Law No. 17505/2013, Environmental Education aims to promote sustainable habits. However, despite being ensured by these documents, it is still a challenge to work on it in an interdisciplinary and contextualized way. In this regard, the investigative problem of this research was to analyze the viability of the Project-Based Learning (PBL) methodology in promoting ecological literacy intended by Formal Environmental Education, in students in the 5th year of an Elementary School – Early Years, in the city of Toledo/PR. Therefore, an educational Action Research was carried out, using techniques of Bibliographic Survey, Documentary Research, Field Research and Content Analysis Technique. Among the main results, it is argued that the PBL methodology contributed to the development of ecological literacy, as, through the proposed methodological approaches, it was possible to promote the development of autonomy skills, proactivity, group work and curiosity for solving problems in participating students. Such skills are important and necessary for ecological literacy and can enable the formation of a student with the ability to read and understand the world, understand the relationships between society and the environment and have assertive attitudes towards the environment in which they live, thus promoting a new type of culture in society, more focused and concerned about the environment.